AKIBAT HUKUM DARI PERKAWINAN DI BAWAH TANGAN (STUDI KASUS PUTUSAN NOMOR 40/PDT.P/2018/PA.WSB - Misbahul Huda (IBLAM Law Review)
Marriage is one of the sacred covenants of a man with a woman to form a happy family. Marriage is a sacred thing because marriage is the beginning of building a household. In Indonesia, marriage has been regulated in Law Number 16 of  2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage.  prove that marriage is important in society. Everyone who wants to get married  must meet the requirements that have been determined by law such as age limit the marriage must be of the same religion and the marriage is recorded. The goal  is that every marriage does not violate applicable norms and is also  administratively orderly. The formulation of the problem: 1). What are the legal  consequences of underhanded marriage? And what is the basis for the  consideration of the Panel of Judges in deciding case number  40/Pdt.P/2018/PA.Wsb? The research method of this thesis is normative juridical,  meaning that the issues raised, discussed and described in this research is focused  on applying the rules or norms in positive law. In this study, the legal  consequences of underhanded marriages, even though they are considered valid  in religion or belief, are marriages conducted outside the knowledge and  supervision of the marriage registrar, and do not have permanent legal force and  are considered invalid in the eyes of state law. The legal consequences of  marriage, one of which results when children enter school age when registered,  every educational institution always requires the registrant (children's parents)  one of which is a birth certificate. The requirement to make a child's birth  certificate is a marriage book and the person who has a marriage book is the  person who when holding the marriage contract registers his marriage.